Daylighting the Environmental Social Sciences for Coastal Management: Introduction to the Special Issue - Sara Jo Breslow; Rebecca Hollender; David J. Trimbach; Tomas M. Koontz; Michael H. Chang; Robert M. Anderson; Mary Ann Rozance; Julie Watson; Kyle Clifton; Maura Flight; Robby Fonner; Connor Lewis-Smith; et al. (Coastal Management, 2026)

Evaluating groundwater quality influences from oil field operations and other anthropogenic activities in an urban setting, Santa Fe Springs, California - Michael T. Wright; Tracy A. Davis; Matthew K. Landon; Michael T. Land; David H. Shimabukuro; Theron A. Sowers; Megan E. Schmer; Riley S. Gannon; Justin T. Kulongoski; Andrew G. Hunt; Elise Watson (Science of The Total Environment, 2026)

A systematic literature inventory on the interaction between dietary factors and environmental chemical exposures for nervous system health outcomes - Chelsea A. Weitekamp; Caleb Watson; Ellen Hata; Kirstin Hester; Urmila P. Kodavanti; Christopher Lau; David M. Lehmann; Colette N. Miller; Rachel M. Shaffer; Fatima Soliman; Martha Powers; Francesca M. Branch (Food and Chemical Toxicology, 2026)

A primary care pharmacogenetic precision medicine pilot based on specific Māori tribal ethical frameworks and principles - Stephen P. Robertson; Benjamin J. Halliday; Rhonda Tibble; Caroline Koia; Tuta Haereroa; Elizabeth Goodin; Ben Curran; Claire E. Rye; Helen Wihongi; Ben Te Aika; Joep de Ligt; Donia Macartney-Coxson; et al. (Journal of Community Genetics, 2026)
Indigenous tribal communities are frequently underserved by genomic medicine because they are under-represented in research, often live in remote locations and have ethical and cultural perspectives that vary from westernised standpoints. The Rakeiora platform, a permissioning and analytical environment that incorporates Māori perspectives and ethical frameworks on how precision medicine research is best conducted was used to host a pharmacogenetic exemplar project to demonstrate proof of principle in a tribal community. The project was prospectively co-designed alongside community representatives through an extensive series of kanohi ki te kanohi (face-to-face) consultation hui, drawing on the strengths, insights, and aspirations of the community. Narratives socialising the study were metaphorically located in tribal-specific histories to improve participation. The cohort of 148 Māori individuals consented to have variants in CYP2C19 extracted from whole genome sequence datasets and correlated to the medicines they were prescribed and had dispensed over a 12-month period. Genotyping indicated that 7% of the cohort were genotypically predicted to be “poor metabolisers” and 11% “rapid metabolisers” of at least one drug known to be processed by CYP2C19. Based on international guidelines, 40% of prescriptions could have benefited from knowledge of the participant’s CYP2C19 genotype through either dose adjustment or prescription of an alternative drug. The study population was broadly supportive of research into precision medicine, but the majority wished to retain ongoing dynamic consent practices mediated by trusted local figures.

Fine‐Scale Ecological Biomonitoring in a Large, Complex Agriculturally Impacted Watershed via eDNA Metabarcoding - Bráulio S. M. L. Silva; Andrew C. Riley; Emilia Craiovan; Michael Wright; Katherine Watson; David R. Lapen; Mehrdad Hajibabaei (Molecular Ecology, 2026)
DNA‐based approaches utilizing high‐throughput sequencing (HTS) (e.g., DNA metabarcoding) have revolutionized ecological biomonitoring by providing higher sample throughput, greater reproducibility, and better cost‐benefits compared to traditional morphology‐based bioassessment studies. Here, we utilized DNA metabarcoding in a watershed in Ontario (Canada) dominated by agricultural land uses. Our aim is to understand patterns of biodiversity in benthic taxa from data generated and inferred at various taxonomic scales and to compare these findings with over a decade of traditional morphological data. We sampled 18 watercourses during summer and fall 2023, spanning a forested‐to‐agricultural land‐use gradient. We found significant differences between metabarcoding and historical morphology data where DNA provided more richness values at both the species ( p = 2 × 10 −5 ) and order ( p = 0.008) levels. Whereas the morphology dataset contained many unresolved taxa, DNA metabarcoding captured a broader taxonomic breadth with diverse genetic profiles among taxa. Non‐metric multidimensional scaling (NMDS) analyses on DNA metabarcoding data produced tighter clusters, more precise separation by land use, and greater consistency across taxonomic scales. Both urban context and land use had significant associations with metabarcoding patterns observed, with differences being strongest between agriculturally‐dominated and primarily forested sites (median R 2 ≈0.08–0.11). We also found strong, consistent environmental signals linked to agricultural settings, such as water conductivity, turbidity, and pH. Altogether, our DNA‐based results demonstrate the differences in community composition among different land uses in this watershed. Importantly, our work highlights the need for more taxonomic resolution (obtained through DNA analysis) to decipher community changes linked to anthropogenic and environmental drivers, as morphological data alone may lack the precision needed to capture these patterns.

Antimicrobial resistance genes in biosolid-amended pasture soils: Insights from a pilot study on a sheep farm - Nuno Silva; Xinyi Huang; Rachael Duncan; Carol Currie; Scott Hamilton; Sophie Lawson; Emily Robertshaw-McFarlane; Eleanor Watson; George King; David A. Ewing; Sarah Brocklehurst; Ruth N. Zadoks; et al. (Journal of Environmental Management, 2026)

Laryngectomy Education and Training Resources: An Environmental Scan of Resources - Laura-Jayne Watson; Emer Fahy; David W. Hamilton; Linda Sharp; Vicky Thornton; Joanne M. Patterson (Journal of Cancer Education, 2026)
In many settings, head and neck cancer (HNC) services are centralized in large hospitals, meaning that community input from HNC specialists can be lacking. Community healthcare professionals often require laryngectomy-specific education and training to provide optimal care to people at home. However, laryngectomy-specific education/training is often sporadic and varies between centres, making it difficult to achieve standardisation in healthcare professionals’ laryngectomy knowledge and skills. This study aimed to identify and critically review existing laryngectomy education/training resources for healthcare professionals, which include elements applicable to community care. We used environmental scanning to systematically and comprehensively identify and examine all available education/training resources which had an element of education and/or training applicable to community laryngectomy care. Eligible resources were reviewed for training-specific details, laryngectomy-specific details, evaluation method, accessibility, and patient and public involvement (PPI). A total of 6655 resources were screened; 49 were eligible for data extraction. There was wide variability in the level of laryngectomy-specific content in the resources. PPI in development was lacking, and data detailing the impact of resources on healthcare professionals’ knowledge/skills and patient outcomes was sparse. This is the first study to systematically identify and appraise laryngectomy education/training resources which have applicability to community care. There is not one consistent approach to education/training development method, content, delivery, or evaluation, likely rendering these ineffective and lacking impact. Community-specific laryngectomy education and training, with clear implementation and evaluation, is required.

A chronological age prediction model using clinical biochemistry and hematological data identifies features of biological age in healthy Labrador retrievers - Carina Salt; Phillip Watson; David Allaway (GeroScience, 2026)

Unlearned responses of chicks, Gallus gallus domesticus, towards aposematic insect-like stimuli - Christopher H. Taylor; David J.G. Watson; Francis Gilbert; David J. Pritchard; John Skelhorn; Tom Reader (Animal Behaviour, 2026)

A critical evaluation of the potential of an online agricultural forum as a space for supporting farmer well-being - Jennifer Howse; David Rose; Katharina Watson; Damian Maye; Lisa Morgans (Journal of Rural Studies, 2026)

Balancing Harvest and Habitat: A Framework for the Sustainable Management of Diadromous Galaxiids - Ben R. J. Crichton; Michael J. H. Hickford; Angus R. McIntosh; David R. Schiel; Andrew S. Watson (New Zealand Journal of Marine and Freshwater Research, 2026)
Managing New Zealand's diadromous Galaxias species and the associated whitebait fishery presents a complex challenge due to species‐specific differences in life‐history strategies, habitat requirements, and population dynamics that underpin responses to anthropogenic and environmental pressures. Consequently, effective management must balance the distinct vulnerabilities and dependencies of each species to ensure long‐term sustainability. This complexity is evident in the fishery's differential impacts, where fishing primarily affects early life stages in kōkopu species but has broader consequences for īnanga populations. The long lifespan of kōkopu species buffers them against short‐term recruitment variation, whereas the annual life cycle of īnanga results in availability of recruits having a direct effect on adult population size. Although fishing closures support larval escapement, the overall benefit to galaxiid populations depends heavily on the quality of habitats that support post‐larval development and adult spawning. An effective management strategy should, therefore, combine targeted fishing regulations with the protection and restoration of high‐quality habitats at regional and national scales to allow sustainable recreational and cultural harvests. This dual approach is critical for sustaining īnanga populations by ensuring sufficient recruits reach adulthood, while also supporting kōkopu by maximising adult carrying capacities and overall population productivity.

Molecular taxonomy of the guitarfish genus Acroteriobatus (Rhinopristiformes: Rhinobatidae) - Mia J. Groeneveld; Juliana D. Klein; Michaela van Staden; Rhett H. Bennett; Matthew L. Dicken; David A. Ebert; Bruce Q. Mann; Kashmika Perumal; Ralph G. A. Watson; Aletta E. Bester-van der Merwe (Marine Biodiversity, 2026)
Guitarfish species (genus Acroteriobatus ) display restricted distributions in undermanaged regions of intense fishing pressure. The importance of accurate specimen identification is well established, especially in the context of conservation management. However, guitarfishes remain poorly understood, which is exacerbated by taxonomic uncertainty due to morphological similarity. We therefore aimed (1) to identify molecular operational taxonomic units (MOTUs) within Acroteriobatus by analysing sampled specimens as well as publicly available sequence data for the cytochrome c oxidase subunit I ( COI ) and nicotinamide adenine dehydrogenase subunit 2 (ND2 ) genes, and (2) to augment and review the representation of these sequences on public databases. A molecular taxonomic approach integrating species delimitation and specimen assignment methods revealed 14 MOTUs. These MOTUs aligned with current species descriptions, displaying no evidence of cryptic diversity. Both genes demonstrated similar interspecific relationships that broadly reflected current distribution ranges, underscoring sub-regional endemism. Moreover, discrepancies in public sequence repositories were identified, attributed to misidentified specimens and the usage of outdated taxonomic nomenclature. Genetic diversity indices were substantially inflated when specimens were grouped based on reported species versus delimited MOTUs, thus overestimating genetic diversity. We highlight the need for extensive, curated DNA reference libraries, including revising earlier sequence entries in light of new taxonomic insights, to enable reliable identification of morphologically conserved species. The molecular resolution illustrated in this study can aid in clarifying taxonomic uncertainties in the genus Acroteriobatus .

Surface-laid pipelines and cables in areas of sand waves and seabed mobility: quantitative analysis from a decade of field observations - Zhechen Hou; Fraser Bransby; David White; Phillip Watson; Andrew Rathbone; Han Eng Low (Ocean Engineering, 2026)

Time dependence of sediment accretion rates: Short- and long-term variability in an urban tidal marsh - Faith Echiejile; Kirk Raper; Tracy Elsey-Quirk; David Velinsky; Elizabeth B. Watson (Estuarine, Coastal and Shelf Science, 2025)

Correction: Positive and negative impacts of electrical infrastructure on animal biodiversity: A systematic review - Adam J. Bennett; David M. Watson; Maggie J. Watson (Oecologia, 2025)

The Role of Patient Education in Low Anterior Resection Syndrome: A Systematic Review - P. Tang; R. Tovel; H. Ong; David Proud; Adele Burgess; Eleanor Watson; Wui Yeat Chen; David Lam; Helen Mohan (Journal of Cancer Education, 2025)
Low anterior resection syndrome (LARS) is a significant complication after sphincter-preserving rectal cancer surgery and negatively impacts a patient’s quality of life. Treatment of LARS is multimodal, and many treatments require engagement from the patient. Understanding the complex array of treatment options and the potential additive effects of different therapies can be difficult. This systematic review aims to assess the role of patient education in treatment of LARS in colorectal cancer patients. A systematic literature search was conducted on PubMed, EMBASE and Ovid Medline according to the PRISMA guidelines for articles published from 1946 to October 2023 and registered with PROSPERO: 42,023,434,601. Studies that reported on clinical outcomes of patients with LARS that underwent any educational intervention were included for this review. Results from five publications including 368 patients with LARS were reviewed for analysis. Three interventions were delivered to symptomatic patients postoperatively and two to all patients who underwent low anterior resection preoperatively. Five trial protocols were also included for analysis, including three preoperative and two postoperative interventions Education interventions were often delivered alongside co-interventions such as medications and pelvic floor physiotherapy. Four studies reported improvement of mean LARS scores and quality of life measures related to the education intervention and associated co-interventions. Patient education has a positive impact towards improving functional outcomes in patients with LARS following resection for rectal cancer. In practice, it is often used in conjunction with other interventions. Determining optimal content and delivery methods is a target for future research.

Positive and negative impacts of electrical infrastructure on animal biodiversity: A systematic review - Adam J. Bennett; David M. Watson; Maggie J. Watson (Oecologia, 2025)
Electrical infrastructure networks are predicted to greatly expand in response to the expected 48% increase in global energy demand by 2040. While assessments of electrical infrastructure are abundant, mixed effects on animal diversity have been reported, warranting further evaluation to determine true effects. We conducted a systematic literature review covering individual, population, and community-level assessments to determine the impacts posed to animal biodiversity by electrical infrastructure and the measures to reduce impacts. Our results show that the literature around electrical infrastructure and animal biodiversity has grown exponentially since the start of the millennium and is biased towards birds and mammals in economically developed countries. We found the majority of reported impacts were negative, occurring primarily through barrier effects (collision) and use of linear features as a resource (electrocution), causing significant population impacts in select species. However, we also found that electrical infrastructure provided positive effects (increased habitat provisioning) to certain taxonomic groups (e.g. corvids, storks), which suggests the potential to encourage conservation efforts using appropriate mitigation on electrical infrastructure. We found the majority of current literature detailed mitigation measures focused on reducing collisions through line (51%) and tower alterations (30%), but often omitted the impacts of EMF, noise, and UV, indicating significant knowledge gaps. On a wider scale, we found that mortality from electrical infrastructure ranked lower than building collisions and predation from feral cats, but remained higher than other anthropogenic energy sources, indicating the potential to cause significant impacts to large-bodied bird species if not addressed.

Reversing and controlling microbial proliferation in the water system of a high-risk hospital ward after extended closure and reconstruction - Dominique L. Chaput; Kerr Clarkson; Linda Bagrade; Aleksandra Marek; Dennis Kelly; David Watson; Tom Steele; Alistair Leanord (Water Research, 2025)

Half of the habitat of Australia's highly imperilled narrow-range species is outside protected areas - Michelle Ward; Martine Maron; Jeremy S. Simmonds; Mark Lintermans; Nick S. Whiterod; David G. Chapple; Hugh P. Possingham; Sarah M. Legge; Rachael V. Gallagher; Brendan A. Wintle; Samantha Vine; Kita Ashman; et al. (Biological Conservation, 2025)

Mechanically coupled distributed dynamic strain measurement for track systems and earthworks - David Milne; Ali Masoudi; John Harkness; Ben Lee; Geoff Watson; Louis Le Pen; Gilberto Brambilla; William Powrie (Transportation Geotechnics, 2025)

On solid ground: Assessing the scale-up potential of structural stone in the UK - Charlotte Taylor; Hannah Gold; David Watson; Anthony Darby; Richard Ball; Tim Ibell; Will Hawkins (Resources Policy, 2025)

Comprehensive Characterisation of the RFC1 Repeat in an Australian Cohort - Kayli C. Davies; Haloom Rafehi; Liam G. Fearnley; Penny Snell; Greta Gillies; Tess A. Field; Gábor M. Halmágyi; Kishore R. Kumar; Kate Pope; Renee Smyth; Susan E. Tomlinson; Stephen Tisch; et al. (The Cerebellum, 2025)

Genomic repercussions of landscape modification on three lizard species - Dylan M. Westaway; Dale G. Nimmo; Chris J. Jolly; Damian R. Michael; David M. Watson; Brenton von Takach (Conservation Genetics, 2025)
Habitat destruction is the most pervasive threat to global biodiversity, leading to widespread population declines and range reductions. Land clearing can leave small, isolated populations persisting in remnant habitat, where demographic factors may erode genomic diversity and diminish adaptive potential. We compared the genomic structure, diversity, inbreeding and effective population sizes of fragmented populations on farms to nearby populations in large, continuous tracts of vegetation (national park) for three terrestrial lizard species in south-eastern Australia. Due to the small spatial scale of the study, observed levels of genomic differentiation among sampling locations were typically very low ( F ST < 0.1). The farm locality of one species, the painted dragon ( Ctenophorus pictus ), showed substantially more differentiation to national park localities ( F ST > 0.05) than the national park localities showed to one another ( F ST < 0.01), suggestive of genetic isolation due to the agricultural matrix. Genomic diversity and effective population sizes were lower in farm populations compared to national parks for two of the three species, the exception being shrubland morethia ( Morethia obscura ), where genomic diversity was similar across site types. Inbreeding coefficients were generally comparable between farm and national park populations. Our findings highlight the genetic consequences of land clearing including low population size, low genomic diversity and higher risk of inbreeding depression. Despite these challenges, habitat fragments can maintain high biodiversity value, which can be maximised by management initiatives such as translocations and establishing habitat corridors.

Quantifying taxon-specific habitat connectivity requirements of urban wildlife using structured expert judgement - Stephanie K. Courtney Jones; Luke S. O'Loughlin; Danswell Starrs; Jacinta E. Humphrey; Stephanie A. Pulsford; Hugh Allan; Matt Beitzel; Kym Birgen; Suzi Bond; Jenny Bounds; Deborah Bower; Renee Brawata; et al. (Biological Conservation, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Legal landscape and a few case studies of natural products’ sales in India: challenges and resolutions - P. Jeya Sheela; D. Abiya Chelliah; Sherrie Jesulyn David; J. Winfred Jebaraj; Esther Watson; Amutha M. (Natural Product Research, 2025)

Managing wilding pines in the Cape Floristic Region, South Africa: Progress and prospects - Grant Martin; Kim Canavan; Gerald Chikowore; Richard Bugan; Willem De Lange; Ben du Toit; Graham Harding; Ronald Heath; Martin Hill; Brett P. Hurley; Philip Ivey; Debbie Muir; et al. (South African Journal of Botany, 2025)

Towards a prioritization screening framework for chemicals, wastes, and pollution - Richard Fuller; David Hanrahan; Victor Kabay; Ernesto Sanchez-Triana; Martin Kayser; Wilfred Lunga; Peter Bridgewater; Robert Watson (Environmental Science & Policy, 2025)

The reliability of pre-deformation to control lateral buckling of pipelines: An evaluation based on observed embedment trends - Jayden Chee; Phil Watson; David White; Alastair Walker (Ocean Engineering, 2024)

An inception framework hypothesis for karst development in the Burren, Ireland - Robert A. Watson; Colin Bunce; David Drew; Simone Fiaschi; Caoimhe Hickey; John Walsh; Eoghan P. Holohan (Geomorphology, 2024)

Wildlife restoration in fragmented landscapes: Trialling wild-to-wild translocation with two common reptiles - Dylan M. Westaway; Chris J. Jolly; David M. Watson; Maggie J. Watson; Damian R. Michael; Grant D. Linley; Ben Holmes; Euan G. Ritchie; Anne Buchan; Ella Loeffler; Dale G. Nimmo (Biological Conservation, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Padded Helmet Shell Covers in American Football: A Comprehensive Laboratory Evaluation with Preliminary On-Field Findings - Nicholas J. Cecchi; Ashlyn A. Callan; Landon P. Watson; Yuzhe Liu; Xianghao Zhan; Ramanand V. Vegesna; Collin Pang; Enora Le Flao; Gerald A. Grant; Michael M. Zeineh; David B. Camarillo (Annals of Biomedical Engineering, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Southern Flounder: Major Milestones and Remaining Knowledge Gaps in Their Biology, Ecology, and Fishery Management - Stephen R. Midway; Frederick S. Scharf; Michael A. Dance; Nancy J. Brown-Peterson; Joseph C. Ballenger; Nicolette S. Beeken; Russell J. Borski; Tanya L. Darden; Kenneth A. Erickson; Troy M. Farmer; Ashley Fincannon; John Godwin; et al. (Reviews in Fisheries Science & Aquaculture, 2024)

Staphylococcal carriage among captive dingoes (Canis dingo) in Victoria, Australia - Sarah M. Wigmore; Scott A. Nankervis; Lynette Watson; David C. Bean (Veterinary Microbiology, 2024)

Assessing the effect of intercropped leguminous service crops on main crops and soil processes using APSIM NG - Elsa Lagerquist; Iris Vogeler; Uttam Kumar; Göran Bergkvist; Marcos Lana; Christine A. Watson; David Parsons (Agricultural Systems, 2024)

The UN Joint Group of Experts on the Scientific Aspects of Marine Environmental Protection (GESAMP) — An ocean science-policy interface standing the test of time - Wendy M. Watson-Wright; Peter G. Wells; Robert A. Duce; Kirsten V. Gilardi; Alexander S.T. Girvan; Michael E. Huber; Peter J. Kershaw; Jan B.H.J. Linders; Richard J. Luit; Chris M.G. Vivian; David H. Vousden (Marine Pollution Bulletin, 2024)

Developing expert scientific consensus on the environmental and societal effects of marine artificial structures prior to decommissioning - Antony M. Knights; Anaëlle J. Lemasson; Louise B. Firth; Todd Bond; Jeremy Claisse; Joop W.P. Coolen; Andrea Copping; Jennifer Dannheim; Michela De Dominicis; Steven Degraer; Michael Elliott; Paul G. Fernandes; et al. (Journal of Environmental Management, 2024)

Development of an open-source carbon footprint calculator of the UK craft brewing value chain - Alexander L. Bowler; Sarah Rodgers; Fanran Meng; Jon McKechnie; David J. Cook; Nicholas J. Watson (Journal of Cleaner Production, 2024)

To what extent can decommissioning options for marine artificial structures move us toward environmental targets? - Antony M. Knights; Anaëlle J. Lemasson; Louise B. Firth; Nicola Beaumont; Silvana Birchenough; Jeremy Claisse; Joop W.P. Coolen; Andrea Copping; Michela De Dominicis; Steven Degraer; Michael Elliott; Paul G. Fernandes; et al. (Journal of Environmental Management, 2024)

Unit cell distortion of ferrierite induced by carbonaceous deposits during skeletal isomerization of 1-butene - Karoline L. Hebisch; Pawel A. Chmielniak; Rick Watson; David Leyshon; Barbara Kimmich; Rui Xu; Benjamin Galfond; Carsten Sievers (Chemical Engineering Journal, 2023)

Isopropyl alcohol inhalation versus 5-HT3 antagonists for treatment of nausea: a meta-analysis of randomised controlled trials - James S. Kimber; Joshua G. Kovoor; John M. Glynatsis; Samuel J. West; Thi Thien Nhi Mai; Jonathan Henry W. Jacobsen; Christopher D. Ovenden; Stephen Bacchi; Joseph N. Hewitt; Aashray K. Gupta; Suzanne Edwards; Fiona J. Taverner; et al. (European Journal of Clinical Pharmacology, 2023)
Purpose Nausea is a common and unpleasant sensation for which current therapies such as serotonin (5-HT 3 ) antagonists are often ineffective, while also conferring a risk of potential adverse events. Isopropyl alcohol (IPA) has been proposed as a treatment for nausea. We aimed to compare IPA with 5-HT 3 antagonists for the treatment of nausea across all clinical settings. Methods MEDLINE, EMBASE, PubMed, CENTRAL and CINAHL were searched from inception to 17 July 2023 for randomised controlled trials (RCTs) comparing inhaled IPA and a 5-HT 3 antagonist for treatment of nausea. Severity and duration of nausea, rescue antiemetic use, adverse events and patient satisfaction were the outcomes sought. Risk of bias (RoB) was assessed using Cochrane RoB 2. Random-effects model was used for meta-analysis. Combination of meta-analyses and narrative review was used to synthesise findings. The evidence was appraised using GRADE. Results From 1242 records, 4 RCTs were included with 382 participants. Participants receiving IPA had a significantly lower mean time to 50% reduction in nausea (MD − 20.06; 95% CI − 26.26, − 13.85). Nausea score reduction at 30 min was significantly greater in the IPA group (MD 21.47; 95% CI 15.47, 27.47). IPA led to significantly reduced requirement for rescue antiemetics (OR 0.60; 95% CI 0.37, 0.95; p = 0.03). IPA led to no significant difference in patient satisfaction when compared with a 5-HT 3 antagonist. The overall GRADE assessment of evidence quality ranged from very low to low. Conclusion IPA may provide rapid, effective relief of nausea when compared with 5-HT 3 antagonists.

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Combined effects of loneliness and inflammation on depression in people with HIV - Mariam A. Hussain; C. Wei-Ming Watson; Erin E. Morgan; Robert K. Heaton; Scott L. Letendre; Dilip V. Jeste; David J. Moore; Jennifer E. Iudicello (Journal of NeuroVirology, 2023)
Objective Loneliness is prevalent in people with HIV (PWH) and associated with adverse health-related consequences, including depression. Chronic inflammation has been linked to depression in PWH, though its association with loneliness is less well established. Simultaneous examination of inflammation, loneliness and depression is needed to clarify these relationships. This study investigated the relationship between loneliness and inflammation, and the effects of loneliness and inflammation on depression in PWH. Methods 82 PWH who were on suppressive ART (mean age [SD] = 53.2 [9.0]) completed the UCLA Loneliness Scale-Version 3 and the Center for Epidemiologic Studies Depression Scale as part of a comprehensive evaluation. Biomarkers of systemic inflammation (CRP, IL-6, CCL2/MCP-1, sCD14) and coagulation (D-dimer) were measured in blood using commercial immunoassays. Results Multivariable linear regression analyses revealed that higher D-dimer, CCL2/MCP-1, and sCD14 were significant predictors of loneliness ( p s < .05) while accounting for relevant covariates. Stepwise multiple linear regression models that included loneliness, biomarkers, and their interactions as predictors of depressive symptoms revealed significant main effects of loneliness and CCL2/MCP-1 levels ( p s < .05), and a significant loneliness by D-dimer interaction ( p < .05) whereby higher D-dimer was associated with increased depressive symptoms only at higher levels of loneliness. Conclusions Increased coagulation activity is associated with loneliness, and in the context of loneliness, may increase risk for depression. Increased inflammation was associated with depression suggesting potentially dissociable underlying biological processes. To the extent that these processes are modifiable, such findings could have important implications in the treatment of loneliness and depression in PWH.

The benefits and pitfalls of machine learning for biomarker discovery - Sandra Ng; Sara Masarone; David Watson; Michael R. Barnes (Cell and Tissue Research, 2023)
Prospects for the discovery of robust and reproducible biomarkers have improved considerably with the development of sensitive omics platforms that can enable measurement of biological molecules at an unprecedented scale. With technical barriers to success lowering, the challenge is now moving into the analytical domain. Genome-wide discovery presents a problem of scale and multiple testing as standard statistical methods struggle to distinguish signal from noise in increasingly complex biological systems. Machine learning and AI methods are good at finding answers in large datasets, but they have a tendency to overfit solutions. It may be possible to find a local answer or mechanism in a specific patient sample or small group of samples, but this may not generalise to wider patient populations due to the high likelihood of false discovery. The rise of explainable AI offers to improve the opportunity for true discovery by providing explanations for predictions that can be explored mechanistically before proceeding to costly and time-consuming validation studies. This review aims to introduce some of the basic concepts of machine learning and AI for biomarker discovery with a focus on post hoc explanation of predictions. To illustrate this, we consider how explainable AI has already been used successfully, and we explore a case study that applies AI to biomarker discovery in rheumatoid arthritis, demonstrating the accessibility of tools for AI and machine learning. We use this to illustrate and discuss some of the potential challenges and solutions that may enable AI to critically interrogate disease and response mechanisms.

Physical and numerical investigation of integral bridge abutment stiffness due to seasonal thermal loading - Sha Luo; Ziyan Huang; Yazan Asia; Flavia De Luca; Raffaele De Risi; John Harkness; Louis Le Pen; Geoff Watson; David Milne; David Chapman; Anastasios Sextos; Nicole Metje; et al. (Transportation Geotechnics, 2023)

Bayesian and ultrasonic sensor aided multi-objective optimisation for sustainable clean-in-place processes - Alexander L. Bowler; Sarah Rodgers; David J. Cook; Nicholas J. Watson (Food and Bioproducts Processing, 2023)

OME-Zarr: a cloud-optimized bioimaging file format with international community support - Josh Moore; Daniela Basurto-Lozada; Sébastien Besson; John Bogovic; Jordão Bragantini; Eva M. Brown; Jean-Marie Burel; Xavier Casas Moreno; Gustavo de Medeiros; Erin E. Diel; David Gault; Satrajit S. Ghosh; et al. (Histochemistry and Cell Biology, 2023)
A growing community is constructing a next-generation file format (NGFF) for bioimaging to overcome problems of scalability and heterogeneity. Organized by the Open Microscopy Environment (OME), individuals and institutes across diverse modalities facing these problems have designed a format specification process (OME-NGFF) to address these needs. This paper brings together a wide range of those community members to describe the cloud-optimized format itself—OME-Zarr—along with tools and data resources available today to increase FAIR access and remove barriers in the scientific process. The current momentum offers an opportunity to unify a key component of the bioimaging domain—the file format that underlies so many personal, institutional, and global data management and analysis tasks.

Birds groom more in regions with higher parasite pressure: a comparison of temperate and subtropical American kestrels - Sarah E. Bush; Matthew M. Waller; Jordan M. Herman; Kristen S. Hobbs; Austin R. Clayton; Jesse L. Watson; M. David Oleyar; Dale H. Clayton (Animal Behaviour, 2023)

A global analysis of avian island diversity–area relationships in the Anthropocene - Thomas J. Matthews; Joseph P. Wayman; Robert J. Whittaker; Pedro Cardoso; Julian P. Hume; Ferran Sayol; Konstantinos Proios; Thomas E. Martin; Benjamin Baiser; Paulo A. V. Borges; Yasuhiro Kubota; Luiz dos Anjos; et al. (Ecology Letters, 2023)
Research on island species–area relationships (ISAR) has expanded to incorporate functional (IFDAR) and phylogenetic (IPDAR) diversity. However, relative to the ISAR, we know little about IFDARs and IPDARs, and lack synthetic global analyses of variation in form of these three categories of island diversity–area relationship (IDAR). Here, we undertake the first comparative evaluation of IDARs at the global scale using 51 avian archipelagic data sets representing true and habitat islands. Using null models, we explore how richness‐corrected functional and phylogenetic diversity scale with island area. We also provide the largest global assessment of the impacts of species introductions and extinctions on the IDAR. Results show that increasing richness with area is the primary driver of the (non‐richness corrected) IPDAR and IFDAR for many data sets. However, for several archipelagos, richness‐corrected functional and phylogenetic diversity changes linearly with island area, suggesting that the dominant community assembly processes shift along the island area gradient. We also find that archipelagos with the steepest ISARs exhibit the biggest differences in slope between IDARs, indicating increased functional and phylogenetic redundancy on larger islands in these archipelagos. In several cases introduced species seem to have ‘re‐calibrated’ the IDARs such that they resemble the historic period prior to recent extinctions.

Ocean carbon from space: Current status and priorities for the next decade - Robert J.W. Brewin; Shubha Sathyendranath; Gemma Kulk; Marie-Hélène Rio; Javier A. Concha; Thomas G. Bell; Astrid Bracher; Cédric Fichot; Thomas L. Frölicher; Martí Galí; Dennis Arthur Hansell; Tihomir S. Kostadinov; et al. (Earth-Science Reviews, 2023)

Evaluating Thin-Layer Sediment Placement as a Tool for Enhancing Tidal Marsh Resilience: a Coordinated Experiment Across Eight US National Estuarine Research Reserves - Kenneth B. Raposa; Andrea Woolfolk; Charlie A. Endris; Monique C. Fountain; Gregg Moore; Megan Tyrrell; Rebecca Swerida; Scott Lerberg; Brandon J. Puckett; Matthew C. Ferner; Jeffrey Hollister; David M. Burdick; et al. (Estuaries and Coasts, 2023)

Community‐based monitoring, assessment and management of data‐limited inland fish stocks in North Rupununi, Guyana - Samuel Shephard; Kevin Edwards; Susan George; Elvis Joseph; Samantha James; Oswin David; Addevi Persaud; L. Cynthia Watson; Nathalie Van Vliet (Fisheries Management and Ecology, 2023)
Inland fisheries are important for food security in communities around the world, especially in developing countries. In North Rupununi, Guyana, the state of exploited stocks is poorly understood, and fishery monitoring and assessment are challenging because diverse fishing gears and target species are distributed across a heterogeneous landscape. This complexity created an opportunity for community‐based monitoring (CBM) to support data‐limited assessment. Standardised CBM was established for the North Rupununi as part of a new inland fisheries management plan initiated by indigenous community groups with support from the government. Quantitative length‐based assessments undertaken for target stocks suggested moderate levels of exploitation consistent with local perception. Our study highlights that local experts and community participants with different levels of training can collect accurate biodiversity data. Further development of CBM is important in North Rupununi. We recommend using local ecological knowledge indicators to track spatial and temporal patterns in exploitation and fish stock status.

Correction: Identifying Factors Associated with Head Impact Kinematics and Brain Strain in High School American Football via Instrumented Mouthguards - Nicholas J. Cecchi; August G. Domel; Yuzhe Liu; Eli Rice; Rong Lu; Xianghao Zhan; Zhou Zhou; Samuel J. Raymond; Sohrab Sami; Heer Singh; India Rangel; Landon P. Watson; et al. (Annals of Biomedical Engineering, 2023)

Threat-abatement framework confirms habitat retention and invasive species management are critical to conserve Australia's threatened species - Stephen G. Kearney; James E.M. Watson; April E. Reside; Diana O. Fisher; Martine Maron; Tim S. Doherty; Sarah M. Legge; John C.Z. Woinarski; Stephen T. Garnett; Brendan A. Wintle; Euan G. Ritchie; Don A. Driscoll; et al. (Biological Conservation, 2023)

Better understand past, present and future climate variability by linking water isotopes and conventional hydrometeorology: summary and recommendations from the International Atomic Energy Agency and World Meteorological Organization - Yuliya Vystavna; Johannes Cullmann; Keith Hipel; Jodie Miller; David X. Soto; Astrid Harjung; Andrew Watson; Alexandra Mattei; Seifu Kebede; Maksym Gusyev (Isotopes in Environmental and Health Studies, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Interpretable machine learning for genomics - David S. Watson (Human Genetics, 2022)
High-throughput technologies such as next-generation sequencing allow biologists to observe cell function with unprecedented resolution, but the resulting datasets are too large and complicated for humans to understand without the aid of advanced statistical methods. Machine learning (ML) algorithms, which are designed to automatically find patterns in data, are well suited to this task. Yet these models are often so complex as to be opaque, leaving researchers with few clues about underlying mechanisms. Interpretable machine learning (iML) is a burgeoning subdiscipline of computational statistics devoted to making the predictions of ML models more intelligible to end users. This article is a gentle and critical introduction to iML, with an emphasis on genomic applications. I define relevant concepts, motivate leading methodologies, and provide a simple typology of existing approaches. I survey recent examples of iML in genomics, demonstrating how such techniques are increasingly integrated into research workflows. I argue that iML solutions are required to realize the promise of precision medicine. However, several open challenges remain. I examine the limitations of current state-of-the-art tools and propose a number of directions for future research. While the horizon for iML in genomics is wide and bright, continued progress requires close collaboration across disciplines.

Acoustic restoration: Using soundscapes to benchmark and fast‐track recovery of ecological communities - Elizabeth Znidersic; David M. Watson (Ecology Letters, 2022)
We introduce a new approach—acoustic restoration—focusing on the applied utility of soundscapes for restoration, recognising the rich ecological and social values they encapsulate. Broadcasting soundscapes in disturbed areas can accelerate recolonisation of animals and the microbes and propagules they carry; long duration recordings are also ideal sources of data for benchmarking restoration initiatives and evocative engagement tools.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Volcano infrasound: progress and future directions - Leighton M. Watson; Alexandra M. Iezzi; Liam Toney; Sean P. Maher; David Fee; Kathleen McKee; Hugo D. Ortiz; Robin S. Matoza; Julia E. Gestrich; Jordan W. Bishop; Alex J. C. Witsil; Jacob F. Anderson; et al. (Bulletin of Volcanology, 2022)
Over the past two decades (2000–2020), volcano infrasound (acoustic waves with frequencies less than 20 Hz propagating in the atmosphere) has evolved from an area of academic research to a useful monitoring tool. As a result, infrasound is routinely used by volcano observatories around the world to detect, locate, and characterize volcanic activity. It is particularly useful in confirming subaerial activity and monitoring remote eruptions, and it has shown promise in forecasting paroxysmal activity at open-vent systems. Fundamental research on volcano infrasound is providing substantial new insights on eruption dynamics and volcanic processes and will continue to do so over the next decade. The increased availability of infrasound sensors will expand observations of varied eruption styles, and the associated increase in data volume will make machine learning workflows more feasible. More sophisticated modeling will be applied to examine infrasound source and propagation effects from local to global distances, leading to improved infrasound-derived estimates of eruption properties. Future work will use infrasound to detect, locate, and characterize moving flows, such as pyroclastic density currents, lahars, rockfalls, lava flows, and avalanches. Infrasound observations will be further integrated with other data streams, such as seismic, ground- and satellite-based thermal and visual imagery, geodetic, lightning, and gas data. The volcano infrasound community should continue efforts to make data and codes accessible and to improve diversity, equity, and inclusion in the field. In summary, the next decade of volcano infrasound research will continue to advance our understanding of complex volcano processes through increased data availability, sensor technologies, enhanced modeling capabilities, and novel data analysis methods that will improve hazard detection and mitigation.

An NMR-Based Metabolomics Assessment of the Effect of Combinations of Natural Feed Items on Juvenile Red Drum, Sciaenops ocellatus - Fabio Casu; David Klett; Justin Yost; Michael R. Denson; Aaron M. Watson (Journal of Marine Science and Engineering, 2022)
This study evaluated the effects of seven diets composed of natural feed components (chopped fish, shrimp, and squid) alone or in combination on the liver metabolite profile of juvenile red drum (Sciaenops ocellatus) cultured in a 24-tank recirculating aquaculture system over the course of 12 weeks using Nuclear Magnetic Resonance (NMR)-based metabolomics. Experimental diets included fish (F), shrimp (SH), squid (SQ), fish and shrimp (FSH), fish and squid (FSQ), shrimp and squid (SHSQ), fish, shrimp, and squid (FSHSQ). A commercial fishmeal-based pelleted diet was used as a control. Fish were fed isocalorically. Red drum liver samples were collected at five different time points: T0, before the start of the trial (n = 12), and subsequently every 3 weeks over the course of 12 weeks (T3, T6, T9, T12), with n = 9 fish/diet/time point. Polar liver extracts were analyzed by NMR-based metabolomics. Multivariate statistical analyses (PCA, PLS-DA) revealed that red drum fed the F diet had a distinct liver metabolite profile from fish fed the other diets, with those fed SH, SQ and the combination diets displaying greater similarities in their metabolome. Results show that 19 metabolites changed significantly among the different dietary treatments, including amino acids and amino acid derivatives, quaternary amines and methylamines, carbohydrates and phospholipids. Specifically, γ-butyrobetaine, N-formimino-L-glutamate (FIGLU), sarcosine and beta-alanine were among the most discriminating metabolites. Significant correlations were found between metabolites and six growth performance parameters (final body weight, total length, condition factor, liver weight, hepatosomatic index, and eviscerated weight). Metabolites identified in this study constitute potential candidates for supplementation in fish feeds for aquaculture and optimization of existing formulations. Additionally, we identified a quaternary amine, γ-butyrobetaine as a potential biomarker of shrimp consumption in red drum. These results warrant further investigation and biomarker validation and have the potential for broader applicability outside of the aquaculture field in future investigations in wild red drum populations and potentially other carnivorous marine fishes.

Relationships between ecosystem properties and sea-level rise vulnerability of tidal wetlands of the U.S. Mid-Atlantic - Tracy Elsey-Quirk; Elizabeth B. Watson; Kirk Raper; Danielle Kreeger; Bhanu Paudel; LeeAnn Haaf; Martha Maxwell-Doyle; Angela Padeletti; Erin Reilly; David J. Velinsky (Environmental Monitoring and Assessment, 2022)

Sediment Accumulation, Elevation Change, and the Vulnerability of Tidal Marshes in the Delaware Estuary and Barnegat Bay to Accelerated Sea Level Rise - LeeAnn Haaf; Elizabeth Burke Watson; Tracy Elsey-Quirk; Kirk Raper; Angela Padeletti; Martha Maxwell-Doyle; Danielle Kreeger; David J. Velinsky (Estuaries and Coasts, 2022)

Development of a Seafloor Community Classification for the New Zealand Region Using a Gradient Forest Approach - Fabrice Stephenson; Ashley A. Rowden; Tom Brough; Grady Petersen; Richard H. Bulmer; John R. Leathwick; Andrew M. Lohrer; Joanne I. Ellis; David A. Bowden; Shane W. Geange; Greig A. Funnell; Debbie J. Freeman; et al. (Frontiers in Marine Science, 2022)
To support ongoing marine spatial planning in New Zealand, a numerical environmental classification using Gradient Forest models was developed using a broad suite of biotic and high-resolution environmental predictor variables. Gradient Forest modeling uses species distribution data to control the selection, weighting and transformation of environmental predictors to maximise their correlation with species compositional turnover. A total of 630,997 records (39,766 unique locations) of 1,716 taxa living on or near the seafloor were used to inform the transformation of 20 gridded environmental variables to represent spatial patterns of compositional turnover in four biotic groups and the overall seafloor community. Compositional turnover of the overall community was classified using a hierarchical procedure to define groups at different levels of classification detail. The 75-group level classification was assessed as representing the highest number of groups that captured the majority of the variation across the New Zealand marine environment. We refer to this classification as the New Zealand “Seafloor Community Classification” (SCC). Associated uncertainty estimates of compositional turnover for each of the biotic groups and overall community were also produced, and an added measure of uncertainty – coverage of the environmental space – was developed to further highlight geographic areas where predictions may be less certain owing to low sampling effort. Environmental differences among the deep-water New Zealand SCC groups were relatively muted, but greater environmental differences were evident among groups at intermediate depths in line with well-defined oceanographic patterns observed in New Zealand’s oceans. Environmental differences became even more pronounced at shallow depths, where variation in more localised environmental conditions such as productivity, seafloor topography, seabed disturbance and tidal currents were important differentiating factors. Environmental similarities in New Zealand SCC groups were mirrored by their biological compositions. The New Zealand SCC is a significant advance on previous numerical classifications and includes a substantially wider range of biological and environmental data than has been attempted previously. The classification is critically appraised and considerations for use in spatial management are discussed.

Protease-activated receptor 2 activation induces behavioural changes associated with depression-like behaviour through microglial-independent modulation of inflammatory cytokines - Serge Moudio; Ashleigh Willis; Karolina Pytka; Roua Abulkassim; Ros R. Brett; Jack F. Webster; Christian Wozny; Mark Barbour; Hui-Rong Jiang; David G. Watson; Josie C. van Kralingen; Scott M. MacKenzie; et al. (Psychopharmacology, 2022)
Rationale Major depressive disorder (MDD) is a leading cause of disability worldwide but currently prescribed treatments do not adequately ameliorate the disorder in a significant portion of patients. Hence, a better appreciation of its aetiology may lead to the development of novel therapies. Objectives In the present study, we have built on our previous findings indicating a role for protease-activated receptor-2 (PAR2) in sickness behaviour to determine whether the PAR2 activator, AC264613, induces behavioural changes similar to those observed in depression-like behaviour. Methods AC264613-induced behavioural changes were examined using the open field test (OFT), sucrose preference test (SPT), elevated plus maze (EPM), and novel object recognition test (NOR). Whole-cell patch clamping was used to investigate the effects of PAR2 activation in the lateral habenula with peripheral and central cytokine levels determined using ELISA and quantitative PCR. Results Using a blood–brain barrier (BBB) permeable PAR2 activator, we reveal that AC-264613 (AC) injection leads to reduced locomotor activity and sucrose preference in mice but is without effect in anxiety and memory-related tasks. In addition, we show that AC injection leads to elevated blood sera IL-6 levels and altered cytokine mRNA expression within the brain. However, neither microglia nor peripheral lymphocytes are the source of these altered cytokine profiles. Conclusions These data reveal that PAR2 activation results in behavioural changes often associated with depression-like behaviour and an inflammatory profile that resembles that seen in patients with MDD and therefore PAR2 may be a target for novel antidepressant therapies.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Prioritizing Beneficial Management Practices for Species at Risk in Agricultural Lands - François Blouin; John F. Wilmshurst; Jeff Harder; Robin Bloom; David W. Johns; Paul Watson (Environmental Management, 2021)

Identifying Factors Associated with Head Impact Kinematics and Brain Strain in High School American Football via Instrumented Mouthguards - Nicholas J. Cecchi; August G. Domel; Yuzhe Liu; Eli Rice; Rong Lu; Xianghao Zhan; Zhou Zhou; Samuel J. Raymond; Sohrab Sami; Heer Singh; India Rangel; Landon P. Watson; et al. (Annals of Biomedical Engineering, 2021)

How groove in music affects gait - Li-Ann Leow; Sarah Watson; David Prete; Kristina Waclawik; Jessica A. Grahn (Experimental Brain Research, 2021)

Araçain, a tyrosol derivative and other phytochemicals from Psidium guineense Sw - Camila Macaúbas-Silva; Maysa D. G. Félix; Ana Karoline S. de Aquino; Paulo G. Pereira-Júnior; Emmily Vieira de O. Brito; Abrahão A. de Oliveira-Filho; John O. Igoli; David G. Watson; Yanna C. F. Teles (Natural Product Research, 2021)

Assessment of the spectral downward irradiance at the surface of the Mediterranean Sea using the radiative Ocean-Atmosphere Spectral Irradiance Model (OASIM) - Paolo Lazzari; Stefano Salon; Elena Terzić; Watson W. Gregg; Fabrizio D'Ortenzio; Vincenzo Vellucci; Emanuele Organelli; David Antoine (Ocean Science, 2021)
A multiplatform assessment of the Ocean–Atmosphere Spectral Irradiance Model (OASIM) radiative model focussed on the Mediterranean Sea for the period 2004–2017 is presented. The BOUée pour l'acquiSition d'une Série Optique à Long termE (BOUSSOLE) mooring and biogeochemical Argo (BGC-Argo) float optical sensor observations are combined with model outputs to analyse the spatial and temporal variabilities in the downward planar irradiance at the ocean–atmosphere interface. The correlations between the data and model are always higher than 0.6. With the exception of downward photosynthetic active radiation and the 670 nm channel, correlation values are always higher than 0.8 and, when removing the inter-daily variability, they are higher than 0.9. At the scale of the BOUSSOLE sampling (15 min temporal resolution), the root mean square difference oscillates at approximately 30 %–40 % of the averaged model output and is reduced to approximately 10 % when the variability between days is filtered out. Both BOUSSOLE and BGC-Argo indicate that bias is up to 20 % for the irradiance at 380 and 412 nm and for wavelengths above 670 nm, whereas it decreases to less than 5 % at the other wavelengths. Analysis of atmospheric input data indicates that the model skill is strongly affected by cloud dynamics. High skills are observed during summer when the cloud cover is low.

Challenges and opportunities for neuroimaging in young patients with traumatic brain injury: a coordinated effort towards advancing discovery from the ENIGMA pediatric moderate/severe TBI group - Emily L Dennis; Karen Caeyenberghs; Robert F Asarnow; Talin Babikian; Brenda Bartnik-Olson; Erin D Bigler; Anthony Figaji; Christopher C Giza; Naomi J Goodrich-Hunsaker; Cooper B Hodges; Kristen R Hoskinson; Marsh Königs; et al. (Brain Imaging and Behavior, 2021)

Optimization and evaluation of fluorescence in situ hybridization chain reaction in cleared fresh-frozen brain tissues - Vivek Kumar; David M. Krolewski; Elaine K. Hebda-Bauer; Aram Parsegian; Brian Martin; Matthew Foltz; Huda Akil; Stanley J. Watson (Brain Structure and Function, 2021)

Atlantic Grey Seal Milk Shows Continuous Changes in Key Metabolites and Indicators of Metabolic Transition in Pups From Birth to Weaning - David G. Watson; Patrick P. Pomeroy; Malcolm W. Kennedy (Frontiers in Marine Science, 2021)
Mothers of the Atlantic grey seal, Halichoerus grypus , lactate for about 20 days, during which they do not feed and may have no access to water. Following weaning, they depart to sea leaving their pups unattended and unfed for up to another 40 days. We are interested in how this lactation strategy supports the pups’ rapid growth and development while also preparing them for their long fast before independently going to sea. We report a broad spectrum metabolomic analysis of whole milks of these seals that reveals continuous changes in key metabolites from birth to weaning. Certain components exhibit abbreviated appearances at the onset of lactation, followed by continuous rises or falls in others until weaning. Riboflavin/Vitamin B2, hormone-related sterol sulfates, lactose, and complex oligosaccharides all appear in milk briefly after birth then disappear. Lipids associated with cellular signaling and brain development occur at highest levels shortly after birth, then diminish. In contrast, other lipids and Vitamin B6/pyridoxine steadily increase as weaning approaches. Overall, these findings may indicate an early transition from carbohydrate to fat-based energy metabolism and establishment of gut microbiomes in pups, followed by provisioning for post-weaning development and fasting.

Pan‐regional marine benthic cryptobiome biodiversity patterns revealed by metabarcoding Autonomous Reef Monitoring Structures - John K. Pearman; Guillem Chust; Eva Aylagas; Ernesto Villarino; James R. Watson; Anne Chenuil; Angel Borja; Abigail E. Cahill; Laura Carugati; Roberto Danovaro; Romain David; Xabier Irigoien; et al. (Molecular Ecology, 2020)
Autonomous Reef Monitoring Structures (ARMS) have been applied worldwide to characterize the critical yet frequently overlooked biodiversity patterns of marine benthic organisms. In order to disentangle the relevance of environmental factors in benthic patterns, here, through standardized metabarcoding protocols, we analyse sessile and mobile ( Amphibalanus , were also shared between the lower salinity seas (Baltic and Black Seas). We found that compositional differences in spatial patterns of rocky‐shore benthos are determined slightly more by dispersal limitation than environmental filtering. Dispersal limitation was similar between sessile and mobile groups, while the sessile group had a larger environmental niche breadth than the mobile group. Further, our study can provide a foundation for future evaluations of biodiversity patterns in the cryptobiome, which can contribute up to 70% of the local biodiversity.

Blunted cardiac output response to exercise in adolescents born preterm - Kristin Haraldsdottir; Andrew M. Watson; David F. Pegelow; Mari Palta; Laura H. Tetri; Taylor Levin; Melissa D. Brix; Ryan M. Centanni; Kara N. Goss; Marlowe M. Eldridge (European Journal of Applied Physiology, 2020)

Global human influence maps reveal clear opportunities in conserving Earth’s remaining intact terrestrial ecosystems - Jason Riggio; Jonathan E. M. Baillie; Steven Brumby; Erle Ellis; Christina M. Kennedy; James R. Oakleaf; Alex Tait; Therese Tepe; David M. Theobald; Oscar Venter; James E. M. Watson; Andrew P. Jacobson (Global Change Biology, 2020)
Leading up to the Convention on Biological Diversity Conference of the Parties 15, there is momentum around setting bold conservation targets. Yet, it remains unclear how much of Earth's land area remains without significant human influence and where this land is located. We compare four recent global maps of human influences across Earth's land, Anthromes, Global Human Modification, Human Footprint and Low Impact Areas, to answer these questions. Despite using various methodologies and data, these different spatial assessments independently estimate similar percentages of the Earth's terrestrial surface as having very low (20%–34%) and low (48%–56%) human influence. Three out of four spatial assessments agree on 46% of the non‐permanent ice‐ or snow‐covered land as having low human influence. However, much of the very low and low influence portions of the planet are comprised of cold (e.g., boreal forests, montane grasslands and tundra) or arid (e.g., deserts) landscapes. Only four biomes (boreal forests, deserts, temperate coniferous forests and tundra) have a majority of datasets agreeing that at least half of their area has very low human influence. More concerning, all datasets. These findings suggest that about half of Earth's terrestrial surface has relatively low human influence and offers opportunities for proactive conservation actions to retain the last intact ecosystems on the planet. However, though the relative abundance of ecosystem areas with low human influence varies widely by biome, conserving these last intact areas should be a high priority before they are completely lost.

Comparative Pro-cognitive and Neurochemical Profiles of Glycine Modulatory Site Agonists and Glycine Reuptake Inhibitors in the Rat: Potential Relevance to Cognitive Dysfunction and Its Management - Kevin C.F. Fone; David J.G. Watson; Rodolphe I. Billiras; Dorothee I. Sicard; Anne Dekeyne; Jean-Michel Rivet; Alain Gobert; Mark J. Millan (Molecular Neurobiology, 2020)
Frontocortical NMDA receptors are pivotal in regulating cognition and mood, are hypofunctional in schizophrenia, and may contribute to autistic spectrum disorders. Despite extensive interest in agents potentiating activity at the co-agonist glycine modulatory site, few comparative functional studies exist. This study systematically compared the actions of the glycine reuptake inhibitors, sarcosine (40–200 mg/kg) and ORG24598 (0.63–5 mg/kg), the agonists, glycine (40–800 mg/kg), and D-serine (10–160 mg/kg) and the partial agonists, S18841 (2.5 mg/kg s.c.) and D-cycloserine (2.5–40 mg/kg) that all dose-dependently prevented scopolamine disruption of social recognition in adult rats. Over similar dose ranges, they also prevented a delay-induced impairment of novel object recognition (NOR). Glycine reuptake inhibitors specifically elevated glycine but not D-serine levels in rat prefrontal cortical (PFC) microdialysates, while glycine and D-serine markedly increased levels of glycine and D-serine, respectively. D-Cycloserine slightly elevated D-serine levels. Conversely, S18841 exerted no influence on glycine, D-serine, other amino acids, monamines, or acetylcholine. Reversal of NOR deficits by systemic S18841 was prevented by the NMDA receptor antagonist, CPP (20 mg/kg), and the glycine modulatory site antagonist, L701,324 (10 mg/kg). S18841 blocked deficits in NOR following microinjection into the PFC (2.5–10 μg/side) but not the striatum. Finally, in rats socially isolated from weaning (a neurodevelopmental model of schizophrenia), S18841 (2.5 and 10 mg/kg s.c.) reversed impairment of NOR and contextual fear-motivated learning without altering isolation-induced hyperactivity. In conclusion, despite contrasting neurochemical profiles, partial glycine site agonists and glycine reuptake inhibitors exhibit comparable pro-cognitive effects in rats of potential relevance to treatment of schizophrenia and other brain disorders where cognitive performance is impaired.

Artificial intelligence supported patient self-care in chronic heart failure: a paradigm shift from reactive to predictive, preventive and personalised care - Matthew Barrett; Josiane Boyne; Julia Brandts; Hans-Peter Brunner-La Rocca; Lieven De Maesschalck; Kurt De Wit; Lana Dixon; Casper Eurlings; Donna Fitzsimons; Olga Golubnitschaja; Arjan Hageman; Frank Heemskerk; et al. (EPMA Journal, 2019)
Heart failure (HF) is one of the most complex chronic disorders with high prevalence, mainly due to the ageing population and better treatment of underlying diseases. Prevalence will continue to rise and is estimated to reach 3% of the population in Western countries by 2025. It is the most important cause of hospitalisation in subjects aged 65 years or more, resulting in high costs and major social impact. The current “one-size-fits-all” approach in the treatment of HF does not result in best outcome for all patients. These facts are an imminent threat to good quality management of patients with HF. An unorthodox approach from a new vision on care is required. We propose a novel predictive, preventive and personalised medicine approach where patients are truly leading their management, supported by an easily accessible online application that takes advantage of artificial intelligence. This strategy paper describes the needs in HF care, the needed paradigm shift and the elements that are required to achieve this shift. Through the inspiring collaboration of clinical and high-tech partners from North-West Europe combining state of the art HF care, artificial intelligence, serious gaming and patient coaching, a virtual doctor is being created. The results are expected to advance and personalise self-care, where standard care tasks are performed by the patients themselves, in principle without involvement of healthcare professionals, the latter being able to focus on complex conditions. This new vision on care will significantly reduce costs per patient while improving outcomes to enable long-term sustainability of top-level HF care.

Source relationships between streambank soils and streambed sediments in a mercury-contaminated stream - Johnbull O. Dickson; Melanie A. Mayes; Scott C. Brooks; Tonia L. Mehlhorn; Kenneth A. Lowe; Jennifer K. Earles; Leroy Goñez-Rodriguez; David B. Watson; Mark J. Peterson (Journal of Soils and Sediments, 2019)

Ethical birding call playback and conservation - David M. Watson; Elizabeth Znidersic; Michael D. Craig (Conservation Biology, 2019)

White matter damage, neuroinflammation, and neuronal integrity in HAND - Aljoharah Alakkas; Ronald J. Ellis; Caitlin Wei-Ming Watson; Anya Umlauf; Robert K. Heaton; Scott Letendre; Ann Collier; Christina Marra; David B. Clifford; Benjamin Gelman; Ned Sacktor; Susan Morgello; et al. (Journal of NeuroVirology, 2019)

Prospects and challenges of environmental DNA (eDNA) monitoring in freshwater ponds - Lynsey R. Harper; Andrew S. Buxton; Helen C. Rees; Kat Bruce; Rein Brys; David Halfmaerten; Daniel S. Read; Hayley V. Watson; Carl D. Sayer; Eleanor P. Jones; Victoria Priestley; Elvira Mächler; et al. (Hydrobiologia, 2019)

Multi-GNSS precise point positioning for precision agriculture - Jing Guo; Xingxing Li; Zhenhong Li; Leyin Hu; Guijun Yang; Chunjiang Zhao; David Fairbairn; David Watson; Maorong Ge (Precision Agriculture, 2018)

Assessment of CNRM coupled ocean-atmosphere model sensitivity to the representation of aerosols - Laura Watson; Martine Michou; Pierre Nabat; David Saint-Martin (Climate Dynamics, 2018)

Sleep apnea and subsequent cancer incidence - Arthur Sillah; Nathaniel F. Watson; Stephen M. Schwartz; David Gozal; Amanda I. Phipps (Cancer Causes & Control, 2018)

Ocean warming has a greater effect than acidification on the early life history development and swimming performance of a large circumglobal pelagic fish - Sue‐Ann Watson; Bridie J. M. Allan; David E. McQueen; Simon Nicol; Darren M. Parsons; Stephen M. J. Pether; Stephen Pope; Alvin N. Setiawan; Neville Smith; Carly Wilson; Philip L. Munday (Global Change Biology, 2018)
Ocean warming and acidification are serious threats to marine life; however, their individual and combined effects on large pelagic and predatory fishes are poorly understood. We determined the effects of projected future temperature and carbon dioxide ( CO 2 ) levels on survival, growth, morphological development and swimming performance on the early life stages of a large circumglobal pelagic fish, the yellowtail kingfish Seriola lalandi . Eggs, larvae and juveniles were reared in cross‐factored treatments of temperature (21 and 25°C) and p CO 2 (500 and 985 μatm) from fertilisation to 25 days post hatching (dph). Temperature had the greatest effect on survival, growth and development. Survivorship was lower, but growth and morphological development were faster at 25°C, with surviving fish larger and more developed at 1, 11 and 21 dph. Elevated p CO 2 affected size at 1 dph, but not at 11 or 21 dph, and did not affect survival or morphological development. Elevated temperature and p CO 2 had opposing effects on swimming performance at 21 dph. Critical swimming speed ( U crit ) was increased by elevated temperature but reduced by elevated p CO 2 . Additionally, elevated temperature increased the proportion of individuals that responded to a startle stimulus, reduced latency to respond and increased maximum escape speed, potentially due to the more advanced developmental stage of juveniles at 25°C. By contrast, elevated p CO 2 reduced the distance moved and average speed in response to a startle stimulus. Our results show that higher temperature is likely to be the primary driver of global change impacts on kingfish early life history; however, elevated p CO 2 could affect critical aspects of swimming performance in this pelagic species. Our findings will help parameterise and structure fisheries population dynamics models and improve projections of impacts to large pelagic fishes under climate change scenarios to better inform adaptation and mitigation responses.

On the use of multicopters for sampling and analysis of volatile organic compounds in the air by adsorption/thermal desorption GC-MS - Jingjing Chen; Austin Scircle; Oscar Black; James V. Cizdziel; Nicola Watson; David Wevill; Ying Zhou (Air Quality, Atmosphere & Health, 2018)

The extent and predictability of the biodiversity–carbon correlation - Moreno Di Marco; James E. M. Watson; David J. Currie; Hugh P. Possingham; Oscar Venter (Ecology Letters, 2018)
Protecting biomass carbon stocks to mitigate climate change has direct implications for biodiversity conservation. Yet, evidence that a positive association exists between carbon density and species richness is contrasting. Here, we test how this association varies (1) across spatial extents and (2) as a function of how strongly carbon and species richness depend on environmental variables. We found the correlation weakens when moving from larger extents, e.g. realms, to narrower extents, e.g. ecoregions. For ecoregions, a positive correlation emerges when both species richness and carbon density vary as functions of the same environmental variables (climate, soil, elevation). In 20% of tropical ecoregions, there are opportunities to pursue carbon conservation with direct biodiversity co‐benefits, while other ecoregions require careful planning for both species and carbon to avoid potentially perverse outcomes. The broad assumption of a linear relationship between carbon and biodiversity can lead to undesired outcomes.

Size, growth, and density data for shallow‐water sea urchins from Mexico to the Aleutian Islands, Alaska, 1956–2016 - Thomas A. Ebert; Louis M. Barr; James L. Bodkin; Dirk Burcham; Dominique Bureau; Henry S. Carson; Nancy L. Caruso; Jennifer E. Caselle; Jeremy T. Claisse; Sabrina Clemente; Kathryn Davis; Paul M. Detwiler; et al. (Ecology, 2018)
Size, growth, and density have been studied for North American Pacific coast sea urchins Strongylocentrotus purpuratus , S. droebachiensis, S. polyacanthus , Mesocentrotus (Strongylocentrotus) franciscanus , Lytechinus pictus , Centrostephanus coronatus , and Arbacia stellata by various workers at diverse sites and for varying lengths of time from 1956 to present. Numerous peer‐reviewed publications have used some of these data but some data have appeared only in graduate theses or the gray literature. There also are data that have never appeared outside original data sheets. Motivation for studies has included fisheries management and environmental monitoring of sewer and power plant outfalls as well as changes associated with disease epidemics. Studies also have focused on kelp restoration, community effects of sea otters, basic sea urchin biology, and monitoring. The data sets presented here are a historical record of size, density, and growth for a common group of marine invertebrates in intertidal and nearshore environments that can be used to test hypotheses concerning future changes associated with fisheries practices, shifts of predator distributions, climate and ecosystem changes, and ocean acidification along the Pacific Coast of North America and islands of the north Pacific. No copyright restrictions apply. Please credit this paper when using the data.

Empirical Dynamic Material Flow Model for Tungsten in the USA - Rachel Watson; Briana Nieradka; David A. Vaccari (Journal of Industrial Ecology, 2018)
Summary Multivariate polynomial regression (MPR) analysis was implemented to develop a nonlinear dynamic material flow model (DMFM) of tungsten in the United States for the years 1975–2000 without assumptions for lifetime distributions within reservoirs. Two external economic factors, the Consumer Price Index and the Industrial Production Index, were included as possible exogenous variables. Six types of vector time‐series models were developed using multilinear, simple interaction, and MPR models, each with and without the exogenous economic variables. The DMFMs developed in this work make one‐step‐ahead predictions. That is, the material flows in a given year were predicted using flows and exogenous variables from previous years. In contrast to approaches that utilize assumed lifetime distributions for material within reservoirs, such as the Weibull distribution, the approach used here is completely data driven. MPR models produced statistically better results than linear models for all 13 flows that were modeled. Four of these models used simple interaction terms (which we call linear interaction terms), and two of these incorporated exogenous variables. The other nine models utilized higher‐degree terms with interactions (called multivariate polynomial terms), and two of these incorporated exogenous variables. We conclude that nonlinear vector time series are capable of identifying complex relationships among material flows and exogenous variables. An understanding of these relationships has potential for managing, conserving, and/or forecasting the use of a resource.

Forest cover and level of protection influence the island-wide distribution of an apex carnivore and umbrella species, the Sri Lankan leopard (Panthera pardus kotiya) - Andrew M. Kittle; Anjali C. Watson; Samuel A. Cushman; David. W. Macdonald (Biodiversity and Conservation, 2018)

Medicago truncatula Oleanolic-Derived Saponins Are Correlated with Caterpillar Deterrence - Fanping Cai; Bonnie S. Watson; David Meek; David V. Huhman; Daniel J. Wherritt; Cecile Ben; Laurent Gentzbittel; Brian T. Driscoll; Lloyd W. Sumner; Jacqueline C. Bede (Journal of Chemical Ecology, 2017)

Toward reassessing data‐deficient species - Lucie M. Bland; Jon Bielby; Stephen Kearney; C. David L. Orme; James E. M. Watson; Ben Collen (Conservation Biology, 2017)
One in 6 species (13,465 species) on the International Union for Conservation of Nature (IUCN) Red List is classified as data deficient due to lack of information on their taxonomy, population status, or impact of threats. Despite the chance that many are at high risk of extinction, data‐deficient species are typically excluded from global and local conservation priorities, as well as funding schemes. The number of data‐deficient species will greatly increase as the IUCN Red List becomes more inclusive of poorly known and speciose groups. A strategic approach is urgently needed to enhance the conservation value of data‐deficient assessments. To develop this, we reviewed 2879 data‐deficient assessments in 6 animal groups and identified 8 main justifications for assigning data‐deficient status (type series, few records, old records, uncertain provenance, uncertain population status or distribution, uncertain threats, taxonomic uncertainty, and new species). Assigning a consistent set of justification tags (i.e., consistent assignment to assessment justifications) to species classified as data deficient is a simple way to achieve more strategic assessments. Such tags would clarify the causes of data deficiency; facilitate the prediction of extinction risk; facilitate comparisons of data deficiency among taxonomic groups; and help prioritize species for reassessment. With renewed efforts, it could be straightforward to prevent thousands of data‐deficient species slipping unnoticed toward extinction.

Quantifying the local influence at a tall tower site in nocturnal conditions - David Werth; Robert Buckley; Gengsheng Zhang; Robert Kurzeja; Monique Leclerc; Henrique Duarte; Matthew Parker; Thomas Watson (Theoretical and Applied Climatology, 2017)

The Diet-related GHG Index: construction and validation of a brief questionnaire-based index - Thomas Bøker Lund; David Watson; Sinne Smed; Lotte Holm; Thomas Eisler; Annemette Nielsen (Climatic Change, 2017)

Ecology under lake ice - Stephanie E. Hampton; Aaron W. E. Galloway; Stephen M. Powers; Ted Ozersky; Kara H. Woo; Ryan D. Batt; Stephanie G. Labou; Catherine M. O'Reilly; Sapna Sharma; Noah R. Lottig; Emily H. Stanley; Rebecca L. North; et al. (Ecology Letters, 2017)
Winter conditions are rapidly changing in temperate ecosystems, particularly for those that experience periods of snow and ice cover. Relatively little is known of winter ecology in these systems, due to a historical research focus on summer ‘growing seasons’. We executed the first global quantitative synthesis on under‐ice lake ecology, including 36 abiotic and biotic variables from 42 research groups and 101 lakes, examining seasonal differences and connections as well as how seasonal differences vary with geophysical factors. Plankton were more abundant under ice than expected; mean winter values were 43.2% of summer values for chlorophyll a , 15.8% of summer phytoplankton biovolume and 25.3% of summer zooplankton density. Dissolved nitrogen concentrations were typically higher during winter, and these differences were exaggerated in smaller lakes. Lake size also influenced winter‐summer patterns for dissolved organic carbon ( DOC ), with higher winter DOC in smaller lakes. At coarse levels of taxonomic aggregation, phytoplankton and zooplankton community composition showed few systematic differences between seasons, although literature suggests that seasonal differences are frequently lake‐specific, species‐specific, or occur at the level of functional group. Within the subset of lakes that had longer time series, winter influenced the subsequent summer for some nutrient variables and zooplankton biomass.

Near‐future pH conditions severely impact calcification, metabolism and the nervous system in the pteropod Heliconoides inflatus - Aurelie Moya; Ella L. Howes; Thomas Lacoue‐Labarthe; Sylvain Forêt; Bishoy Hanna; Mónica Medina; Philip L. Munday; Jue‐Sheng Ong; Jean‐Louis Teyssié; Gergely Torda; Sue‐Ann Watson; David J. Miller; et al. (Global Change Biology, 2016)
Shelled pteropods play key roles in the global carbon cycle and food webs of various ecosystems. Their thin external shell is sensitive to small changes in pH, and shell dissolution has already been observed in areas where aragonite saturation state is ~1. A decline in pteropod abundance has the potential to disrupt trophic networks and directly impact commercial fisheries. Therefore, it is crucial to understand how pteropods will be affected by global environmental change, particularly ocean acidification. In this study, physiological and molecular approaches were used to investigate the response of the Mediterranean pteropod, Heliconoides inflatus , to pH values projected for 2100 under a moderate emissions trajectory ( RCP 6.0). Pteropods were subjected to pH T 7.9 for 3 days, and gene expression levels, calcification and respiration rates were measured relative to pH T 8.1 controls. Gross calcification decreased markedly under low pH conditions, while genes potentially involved in calcification were up‐regulated, reflecting the inability of pteropods to maintain calcification rates. Gene expression data imply that under low pH conditions, both metabolic processes and protein synthesis may be compromised, while genes involved in acid–base regulation were up‐regulated. A large number of genes related to nervous system structure and function were also up‐regulated in the low pH treatment, including a GABA A receptor subunit. This observation is particularly interesting because GABA A receptor disturbances, leading to altered behavior, have been documented in several other marine animals after exposure to elevated CO 2 . The up‐regulation of many genes involved in nervous system function suggests that exposure to low pH could have major effects on pteropod behavior. This study illustrates the power of combining physiological and molecular approaches. It also reveals the importance of behavioral analyses in studies aimed at understanding the impacts of low pH on marine animals.

Preparation of legionaminic acid analogs of sialo-glycoconjugates by means of mammalian sialyltransferases - David C. Watson; Warren W. Wakarchuk; Christian Gervais; Yves Durocher; Anna Robotham; Steve M. Fernandes; Ronald L. Schnaar; N. Martin Young; Michel Gilbert (Glycoconjugate Journal, 2015)

Equipped to deal with uncertainty in climate and impacts predictions: lessons from internal peer review - Anna Wesselink; Andrew Juan Challinor; James Watson; Keith Beven; Icarus Allen; Helen Hanlon; Ana Lopez; Susanne Lorenz; Friederike Otto; Andy Morse; Cameron Rye; Stephane Saux-Picard; et al. (Climatic Change, 2015)

Lessons from China: building technological capabilities for low carbon technology transfer and development - Jim Watson; Rob Byrne; David Ockwell; Michele Stua (Climatic Change, 2015)

The weakness of evidence supporting tropical niche conservatism as a main driver of current richness–temperature gradients - Véronique Boucher‐Lalonde; Rafael Xavier De Camargo; Jean‐Michel Fortin; Shahira Khair; Rachel I. So; Héctor Vázquez Rivera; Dale Watson; Juan Zuloaga; David J. Currie (Global Ecology and Biogeography, 2015)
Aim Geographical variations in species richness are highly correlated with current temperature. The tropical niche conservatism hypothesis proposes that this relationship is driven by the evolutionarily conserved ancestral tolerances of species to the warm environments in which most clades originated. The hypothesis predicts that the slope of the richness–temperature gradient is positively related to the temperature of the period during which the clade originated. Here, we test this prediction for bird and mammal families in the A mericas and by revisiting a global analysis of 343 groups of organisms ( R omdal et al ., 2013, G lobal E cology and B iogeography , 22 , 344–350). Location The A mericas and world‐wide. Methods We computed the slope of the species richness–current temperature relationship within each bird and mammal family in the A mericas. We used palaeoclimate reconstructions to estimate temperature at the time of the family's origination, taken from the fossil record. We then tested how much of the among‐family variance in the richness–temperature slope could be explained by the temperature at the time of family origination. We repeated this test for the 343 groups of organisms world‐wide. Results Contrary to the prediction of tropical niche conservatism, the temperature at which bird and mammal families originated does not explain variations in the richness–temperature relationships. Similarly, we show that, although the predicted relationship was statistically detected in a broad range of groups of organisms in a previous study, it in fact statistically explains only 1.2–2.9% of the variance among groups in the slope of richness gradients. Main conclusions We found evidence inconsistent with the hypothesis that tropical niche conservatism is the main mechanism underlying the ubiquitous richness–climate relationship.

Invertebrate diversity of the unexplored marine western margin of Australia: taxonomy and implications for global biodiversity - Gary C. B. Poore; Lynda Avery; Magda Błażewicz-Paszkowycz; Joanna Browne; Niel L. Bruce; Sarah Gerken; Chris Glasby; Elizabeth Greaves; Anna W. McCallum; David Staples; Anna Syme; Joanne Taylor; et al. (Marine Biodiversity, 2015)

Deployment of Microbial Biosensors to Assess the Performance of Ameliorants in Metal-Contaminated Soils - Snežana P. Maletić; Malcolm A. Watson; Saad Dehlawi; Elizabeth E. Diplock; David Mardlin; Graeme I. Paton (Water, Air, & Soil Pollution, 2015)

The phytotoxicity of ZnO nanoparticles on wheat varies with soil properties - Jean-Luc Watson; Tommy Fang; Christian O. Dimkpa; David W. Britt; Joan E. McLean; Astrid Jacobson; Anne J. Anderson (BioMetals, 2015)

Evidence of land‐sea transfer of the zoonotic pathogen Campylobacter to a wildlife marine sentinel species - Johanna L. Baily; Guillaume Méric; Sion Bayliss; Geoffrey Foster; Simon E. Moss; Eleanor Watson; Ben Pascoe; Jane Mikhail; Romain Pizzi; Robert J. Goldstone; David G. E. Smith; Kim Willoughby; et al. (Molecular Ecology, 2015)
Environmental pollution often accompanies the expansion and urbanization of human populations where sewage and wastewaters commonly have an impact on the marine environments. Here, we explored the potential for faecal bacterial pathogens, of anthropic origin, to spread to marine wildlife in coastal areas. The common zoonotic bacterium Campylobacter was isolated from grey seals ( Halichoerus grypus ), an important sentinel species for environmental pollution, and compared to isolates from wild birds, agricultural sources and clinical samples to characterize possible transmission routes. Campylobacter jejuni was present in half of all grey seal pups sampled (24/50 dead and 46/90 live pups) in the breeding colony on the Isle of May (Scotland), where it was frequently associated with histological evidence of disease. Returning yearling animals (19/19) were negative for C . jejuni suggesting clearance of infection while away from the localized colony infection source. The genomes of 90 isolates from seals were sequenced and characterized using a whole‐genome multilocus sequence typing ( MLST ) approach and compared to 192 published genomes from multiple sources using population genetic approaches and a probabilistic genetic attribution model to infer the source of infection from MLST data. The strong genotype‐host association has enabled the application of source attribution models in epidemiological studies of human campylobacteriosis, and here assignment analyses consistently grouped seal isolates with those from human clinical samples. These findings are consistent with either a common infection source or direct transmission of human campylobacter to grey seals, raising concerns about the spread of human pathogens to wildlife marine sentinel species in coastal areas.

Long Time Series in US Fisheries Oceanography - Sam McClatchie; Janet Duffy-Anderson; John Field; Ralf Goericke; Dave Griffith; David Hanisko; Jonathan Hare; Joanne Lyczkowski-Shultz; William Peterson; William Watson; Edward Weber; Glenn Zapfe (Oceanography, 2014)

Gas chromatography–mass spectrometry analysis of fatty acid profiles of Antarctic and non-Antarctic yeasts - Mohammad Bhuiyan; David Tucker; Kenneth Watson (Antonie van Leeuwenhoek, 2014)

An MRI atlas of the mouse basal ganglia - Jeremy F. P. Ullmann; Charles Watson; Andrew L. Janke; Nyoman D. Kurniawan; George Paxinos; David C. Reutens (Brain Structure and Function, 2014)

Selection of low-variance expressed Malus x domestica (apple) genes for use as quantitative PCR reference genes (housekeepers) - Judith Bowen; Hilary S. Ireland; Ross Crowhurst; Zhiwei Luo; Amy E. Watson; Toshi Foster; Nigel Gapper; Jim J. Giovanonni; James P. Mattheis; Chris Watkins; David Rudell; Jason W. Johnston; et al. (Tree Genetics & Genomes, 2014)

The global contribution of forage fish to marine fisheries and ecosystems - Ellen K Pikitch; Konstantine J Rountos; Timothy E Essington; Christine Santora; Daniel Pauly; Reg Watson; Ussif R Sumaila; P Dee Boersma; Ian L Boyd; David O Conover; Philippe Cury; Selina S Heppell; et al. (Fish and Fisheries, 2014)
Forage fish play a pivotal role in marine ecosystems and economies worldwide by sustaining many predators and fisheries directly and indirectly. We estimate global forage fish contributions to marine ecosystems through a synthesis of 72 published E copath models from around the world. Three distinct contributions of forage fish were examined: (i) the ecological support service of forage fish to predators in marine ecosystems, (ii) the total catch and value of forage fisheries and (iii) the support service of forage fish to the catch and value of other commercially targeted predators. Forage fish use and value varied and exhibited patterns across latitudes and ecosystem types. Forage fish supported many kinds of predators, including fish, seabirds, marine mammals and squid. Overall, forage fish contribute a total of about $16.9 billion USD to global fisheries values annually, i.e. 20% of the global ex‐vessel catch values of all marine fisheries combined. While the global catch value of forage fisheries was $5.6 billion, fisheries supported by forage fish were more than twice as valuable ($11.3 billion). These estimates provide important information for evaluating the trade‐offs of various uses of forage fish across ecosystem types, latitudes and globally. We did not estimate a monetary value for supportive contributions of forage fish to recreational fisheries or to uses unrelated to fisheries, and thus the estimates of economic value reported herein understate the global value of forage fishes.

Continental‐Scale Governance and the Hastening of Loss of Australia's Biodiversity - Euan G. Ritchie; Corey J. A. Bradshaw; Chris R. Dickman; Richard Hobbs; Christopher N. Johnson; Emma L. Johnston; William F. Laurance; David Lindenmayer; Michael A. McCarthy; Dale G. Nimmo; Hugh H. Possingham; Robert L. Pressey; et al. (Conservation Biology, 2013)

Phytochemicals from Cruciferous Vegetables, Epigenetics, and Prostate Cancer Prevention - Gregory W. Watson; Laura M. Beaver; David E. Williams; Roderick H. Dashwood; Emily Ho (The AAPS Journal, 2013)

Mistletoe specialist frugivores: latterday ‘Johnny Appleseeds’ or self-serving market gardeners? - David M. Watson; John Rawsthorne (Oecologia, 2013)

The Application of Science- and Risk-Based Concepts to Drug Substance Stability Strategies - Stephen T. Colgan; Timothy J. Watson; Robert D. Whipple; Roger Nosal; Jon V. Beaman; David M. De Antonis (Journal of Pharmaceutical Innovation, 2012)

Resilience of Norovirus GII.4 to Freezing and Thawing: Implications for Virus Infectivity - Gary P. Richards; Michael A. Watson; Gloria K. Meade; Gregory L. Hovan; David H. Kingsley (Food and Environmental Virology, 2012)

The effect of N fertilizer forms on nitrous oxide emissions from UK arable land and grassland - Keith A. Smith; Karen E. Dobbie; Rachel Thorman; Catherine J. Watson; David R. Chadwick; Sirwan Yamulki; Bruce C. Ball (Nutrient Cycling in Agroecosystems, 2012)

Predictors of survival among patients diagnosed with adenocarcinoma of the esophagus and gastroesophageal junction - Aaron P. Thrift; Christina M. Nagle; Paul P. Fahey; Bernard M. Smithers; David I. Watson; David C. Whiteman (Cancer Causes & Control, 2012)

The Mediterranean Sea under siege: spatial overlap between marine biodiversity, cumulative threats and marine reserves - Marta Coll; Chiara Piroddi; Camille Albouy; Frida Ben Rais Lasram; William W. L. Cheung; Villy Christensen; Vasiliki S. Karpouzi; François Guilhaumon; David Mouillot; Michelle Paleczny; Maria Lourdes Palomares; Jeroen Steenbeek; et al. (Global Ecology and Biogeography, 2012)
Aim A large body of knowledge exists on individual anthropogenic threats that have an impact on marine biodiversity in the Mediterranean Sea, although we know little about how these threats accumulate and interact to affect marine species and ecosystems. In this context, we aimed to identify the main areas where the interaction between marine biodiversity and threats is more pronounced and to assess their spatial overlap with current marine protected areas in the Mediterranean. Location Mediterranean Sea. Methods We first identified areas of high biodiversity of marine mammals, marine turtles, seabirds, fishes and commercial or well‐documented invertebrates. We mapped potential areas of high threat where multiple threats are occurring simultaneously. Finally we quantified the areas of conservation concern for biodiversity by looking at the spatial overlap between high biodiversity and high cumulative threats, and we assessed the overlap with protected areas. Results Our results show that areas with high marine biodiversity in the Mediterranean Sea are mainly located along the central and north shores, with lower values in the south‐eastern regions. Areas of potential high cumulative threats are widespread in both the western and eastern basins, with fewer areas located in the south‐eastern region. The interaction between areas of high biodiversity and threats for invertebrates, fishes and large animals in general (including large fishes, marine mammals, marine turtles and seabirds) is concentrated in the coastal areas of Spain, Gulf of Lions, north‐eastern Ligurian Sea, Adriatic Sea, Aegean Sea, south‐eastern Turkey and regions surrounding the Nile Delta and north‐west African coasts. Areas of concern are larger for marine mammal and seabird species. Main conclusions These areas may represent good candidates for further research, management and protection activities, since there is only a maximum 2% overlap between existing marine protected areas (which cover 5% of the Mediterranean Sea) and our predicted areas of conservation concern for biodiversity.

Structural changes in the hippocampus and amygdala at first episode of psychosis - David R. Watson; Feng Bai; Suzanne L. Barrett; Aidan Turkington; Teresa M. Rushe; Ciaran C. Mulholland; Stephen J. Cooper (Brain Imaging and Behavior, 2012)

Specificity analysis of the C-type lectin from rattlesnake venom, and its selectivity towards Gal- or GalNAc-terminated glycoproteins - N. Martin Young; Henk van Faassen; David C. Watson; C. Roger MacKenzie (Glycoconjugate Journal, 2011)

Polymorphic variants in tenascin-C (TNC) are associated with atherosclerosis and coronary artery disease - Mollie A. Minear; David R. Crosslin; Beth S. Sutton; Jessica J. Connelly; Sarah C. Nelson; Shera Gadson-Watson; Tianyuan Wang; David Seo; Jeffrey M. Vance; Michael H. Sketch; Carol Haynes; Pascal J. Goldschmidt-Clermont; et al. (Human Genetics, 2011)

Isolation by oceanographic distance explains genetic structure for Macrocystis pyrifera in the Santa Barbara Channel - FILIPE ALBERTO; PETER T. RAIMONDI; DANIEL C. REED; JAMES R. WATSON; DAVID A. SIEGEL; SATOSHI MITARAI; NELSON COELHO; ESTER A. SERRÃO (Molecular Ecology, 2011)
Ocean currents are expected to be the predominant environmental factor influencing the dispersal of planktonic larvae or spores; yet, their characterization as predictors of marine connectivity has been hindered by a lack of understanding of how best to use oceanographic data. We used a high‐resolution oceanographic model output and Lagrangian particle simulations to derive oceanographic distances (hereafter called transport times) between sites studied for Macrocystis pyrifera genetic differentiation. We build upon the classical isolation‐by‐distance regression model by asking how much additional variability in genetic differentiation is explained when adding transport time as predictor. We explored the extent to which gene flow is dependent upon seasonal changes in ocean circulation. Because oceanographic transport between two sites is inherently asymmetric, we also compare the explanatory power of models using the minimum or the mean transport times. Finally, we compare the direction of connectivity as estimated by the oceanographic model and genetic assignment tests. We show that the minimum transport time had higher explanatory power than the mean transport time, revealing the importance of considering asymmetry in ocean currents when modelling gene flow. Genetic assignment tests were much less effective in determining asymmetry in gene flow. Summer‐derived transport times, in particular for the month of June, which had the strongest current speed, greatest asymmetry and highest spore production, resulted in the best‐fit model explaining twice the variability in genetic differentiation relative to models that use geographic distance or habitat continuity. The best overall model also included habitat continuity and explained 65% of the variation in genetic differentiation among sites.

A Science and Risk Based Proposal for Understanding Scale and Equipment Dependencies of Small Molecule Drug Substance Manufacturing Processes - David J. am Ende; Christine B. Seymour; Timothy J. N. Watson (Journal of Pharmaceutical Innovation, 2010)

Taking the chaos out of genetic patchiness: seascape genetics reveals ecological and oceanographic drivers of genetic patterns in three temperate reef species - KIMBERLY A. SELKOE; JAMES R. WATSON; CROW WHITE; TAL BEN HORIN; MATTHEW IACCHEI; SATOSHI MITARAI; DAVID A. SIEGEL; STEVEN D. GAINES; ROBERT J. TOONEN (Molecular Ecology, 2010)
Marine species frequently show weak and/or complex genetic structuring that is commonly dismissed as ‘chaotic’ genetic patchiness and ecologically uninformative. Here, using three datasets that individually feature weak chaotic patchiness, we demonstrate that combining inferences across species and incorporating environmental data can greatly improve the predictive value of marine population genetics studies on small spatial scales. Significant correlations in genetic patterns of microsatellite markers among three species, kelp bass Paralabrax clathratus , Kellet’s whelk Kelletia kelletii and California spiny lobster Panulirus interruptus , in the Southern California Bight suggest that slight differences in diversity and pairwise differentiation across sampling sites are not simply noise or chaotic patchiness, but are ecologically meaningful. To test whether interspecies correlations potentially result from shared environmental drivers of genetic patterns, we assembled data on kelp bed size, sea surface temperature and estimates of site‐to‐site migration probability derived from a high resolution multi‐year ocean circulation model. These data served as predictor variables in linear models of genetic diversity and linear mixed models of genetic differentiation that were assessed with information–theoretic model selection. Kelp was the most informative predictor of genetics for all three species, but ocean circulation also played a minor role for kelp bass. The shared patterns suggest a single spatial marine management strategy may effectively protect genetic diversity of multiple species. This study demonstrates the power of environmental and ecological data to shed light on weak genetic patterns and highlights the need for future focus on a mechanistic understanding of the links between oceanography, ecology and genetic structure.

Effects of high-dose B vitamin complex with vitamin C and minerals on subjective mood and performance in healthy males - David O. Kennedy; Rachel Veasey; Anthony Watson; Fiona Dodd; Emma Jones; Silvia Maggini; Crystal F. Haskell (Psychopharmacology, 2010)

Assessment of two methods to monitor wetness to control dust emissions, Owens Dry Lake, California - David P. Groeneveld; Richard P. Watson; David D. Barz; Jeffrey B. Silverman; William M. Baugh (International Journal of Remote Sensing, 2010)

A limited innate immune response is induced by a replication-defective herpes simplex virus vector following delivery to the murine central nervous system - Zane Zeier; J Santiago Aguilar; Cecilia M Lopez; GB Devi-Rao; Zachary L Watson; Henry V Baker; Edward K Wagner; David C Bloom (Journal of NeuroVirology, 2009)

GeoChip‐based analysis of functional microbial communities during the reoxidation of a bioreduced uranium‐contaminated aquifer - Joy D. Van Nostrand; Wei‐Min Wu; Liyou Wu; Ye Deng; Jack Carley; Sue Carroll; Zhili He; Baohua Gu; Jian Luo; Craig S. Criddle; David B. Watson; Philip M. Jardine; et al. (Environmental Microbiology, 2009)
Summary A pilot‐scale system was established for in situ biostimulation of U(VI) reduction by ethanol addition at the US Department of Energy's (DOE's) Field Research Center (Oak Ridge, TN). After achieving U(VI) reduction, stability of the bioreduced U(IV) was evaluated under conditions of (i) resting (no ethanol injection), (ii) reoxidation by introducing dissolved oxygen (DO), and (iii) reinjection of ethanol. GeoChip, a functional gene array with probes for N, S and C cycling, metal resistance and contaminant degradation genes, was used for monitoring groundwater microbial communities. High diversity of all major functional groups was observed during all experimental phases. The microbial community was extremely responsive to ethanol, showing a substantial change in community structure with increased gene number and diversity after ethanol injections resumed. While gene numbers showed considerable variations, the relative abundance (i.e. percentage of each gene category) of most gene groups changed little. During the reoxidation period, U(VI) increased, suggesting reoxidation of reduced U(IV). However, when introduction of DO was stopped, U(VI) reduction resumed and returned to pre‐reoxidation levels. These findings suggest that the community in this system can be stimulated and that the ability to reduce U(VI) can be maintained by the addition of electron donors. This biostimulation approach may potentially offer an effective means for the bioremediation of U(VI)‐contaminated sites.

Accumulation of an organic anticancer selenium compound in a transgenic Solanaceous species shows wider applicability of the selenocysteine methyltransferase transgene from selenium hyperaccumulators - Marian J. McKenzie; Donald A. Hunter; Ranjith Pathirana; Lyn M. Watson; Nigel I. Joyce; Adam J. Matich; Daryl D. Rowan; David A. Brummell (Transgenic Research, 2009)

Galactose metabolism in cell walls of opening and senescing petunia petals - Erin M. O’Donoghue; Sheryl D. Somerfield; Lyn M. Watson; David A. Brummell; Donald A. Hunter (Planta, 2009)

Cost/Benefit Considerations for Recent Saltcedar Control, Middle Pecos River, New Mexico - Dave Barz; Richard P. Watson; Joseph F. Kanney; Jesse D. Roberts; David P. Groeneveld (Environmental Management, 2009)

Dioxin- and POP-contaminated sites—contemporary and future relevance and challenges - Roland Weber; Caroline Gaus; Mats Tysklind; Paul Johnston; Martin Forter; Henner Hollert; Emanuel Heinisch; Ivan Holoubek; Mariann Lloyd-Smith; Shigeki Masunaga; Paolo Moccarelli; David Santillo; et al. (Environmental Science and Pollution Research, 2008)

A thermobarometer for sphene (titanite) - Leslie A. Hayden; E. Bruce Watson; David A. Wark (Contributions to Mineralogy and Petrology, 2008)

Parasites boost productivity: effects of mistletoe on litterfall dynamics in a temperate Australian forest - Wendy A. March; David M. Watson (Oecologia, 2007)

TitaniQ: a titanium-in-quartz geothermometer - David A. Wark; E. Bruce Watson (Contributions to Mineralogy and Petrology, 2006)

Zr-in-rutile thermometry in blueschists from Sifnos, Greece - Frank S. Spear; David A. Wark; John T. Cheney; John C. Schumacher; E. Bruce Watson (Contributions to Mineralogy and Petrology, 2006)

Effect of faceting on pore geometry in texturally equilibrated rocks: implications for low permeability at low porosity - Takashi Yoshino; Jonathan D. Price; David A. Wark; E. Bruce Watson (Contributions to Mineralogy and Petrology, 2006)

Bird community responses to habitat fragmentation: how consistent are they across landscapes? - James E. M. Watson; Robert J. Whittaker; David Freudenberger (Journal of Biogeography, 2005)
Aim The woodland ecosystems of south‐eastern Australia have been extensively disturbed by agriculture and urbanization. Herein, the occurrence of birds in woodland remnants in three distinct landscapes was analysed to examine the effects of different types of landscape matrices on species richness vs. area and species richness vs. isolation relationships and individual species responses to woodland fragmentation. Location The study system comprised three distinct woodland landscapes of the northern Australian Capital Territory and bordering areas of New South Wales. These landscapes (termed agricultural, peri‐urban and urban) are located within 50 km of each other, have remnant fragments of similar age, size, isolation, woodland cover, elevation and climates. The major distinguishing feature of the three landscapes was the properties of the habitats surrounding the numerous woodland remnants. Methods Bird surveys, using an area‐search methodology, were conducted in 1999 and 2000 in 127 remnants in the three landscapes to determine bird species presence/absence. Each remnant was characterized by measures of remnant area, isolation and habitat complexity. To characterize differences between each landscape, we conducted an analysis of the amount of tree cover and human disturbance in each landscape using SPOT imagery and aerial photographs. Linear regressions of woodland‐dependent species richness vs. remnant area and remnant isolation for the three different landscapes were calculated to see if there were any apparent differences. Binomial logistic regressions were used to determine the relationships between the occurrence of each species and the size and isolation of woodland habitat, in each landscape. Results All the landscapes displayed a significant ( P P Main conclusions These results indicate that woodland bird communities have a varying response to habitat fragmentation in different landscapes. Whilst we cannot be sure how representative our chosen landscapes are of other similarly composed landscapes, these results suggest that the type of landscape matrix may have a considerable influence on how bird species are affected by woodland fragmentation in the region. For instance, the properties of a matrix may influence both the resources available in the landscape as a whole for different bird species, and the connectivity (dispersal of birds), between woodland remnants. We encourage further research that examines these hypotheses and argue that the management of the matrix should be included in conservation strategies for fragmented landscapes.

Introduced and cryptogenic species in Port Phillip Bay, Victoria, Australia - Ronald E. Thresher; Richard B. Martin; Sue Boyd; Brian F. Cohen; David R. Currie; Martin F. Gomon; Michael J. Keough; John A. Lewis; Matthew M. Lockett; Nicole Mays; Matthew A. McArthur; Tim D. O'Hara; et al. (Marine Biology, 2004)

Utility of Remote Sensing in Predicting Crop and Soil Characteristics - Chris T. Leon; David R. Shaw; Michael S. Cox; Melinda J. Abshire; Brian Ward; MiLton C. Wardlaw; Clarence Watson (Precision Agriculture, 2003)

Influence of gizzard shad on phytoplankton size and primary productivity in mesocosms and earthen ponds in the southeastern U.S. - David L. Watson; David R. Bayne; Dennis R. DeVries; J. Williams (Hydrobiologia, 2003)

Microbiological Characteristics in a Zero-Valent Iron Reactive Barrier - Baohua Gu; David B. Watson; Liyou Wu; Debra H. Phillips; David C. White; Jizhong Zhou (Environmental Monitoring and Assessment, 2002)

A conceptual framework for studying species composition in fragments, islands and other patchy ecosystems - David M. Watson (Journal of Biogeography, 2002)
Aim I propose and develop a new classification system to explain diversity patterns in habitat fragments, equally applicable to islands and other inherently patchy ecosystems. My primary goal is to provide an inclusive model to improve the comparability of studies and enhance future efforts to synthesize their findings, yielding a generalized basis for understanding species composition in patchy ecosystems. Results Differentiating islands from fragments and incorporating patch age and patch: matrix contrast, eight classes of patch are distinguished, spanning a range of geographical features. To compare studies of diversity patterns among and between patch types, patch biota are divided into three categories based on their origin—relict species (present before fragmentation), matrix‐derived species and interpatch dispersers. Applying this novel scheme to existing data, the effects of insularization are synthesized. Direct comparisons among fragments revealed broad similarity in the long‐term effects of habitat fragmentation compared with highly divergent patterns in younger landscapes ( Main conclusions Although necessarily broad, this framework provides an explicit context within which to test forty‐four specific predictions regarding the distribution of diversity in patchy landscapes and thereby gain a clearer understanding of the long‐term biological consequences of insularization. I propose that the fragments‐as‐islands analogy be revisited, potentially yielding valuable insight into the long‐term future awaiting anthropogenically altered ecosystems.

An Assessment of the Focal-Species Approach for Conserving Birds in Variegated Landscapes in Southeastern Australia - James Watson; David Freudenberger; David Paull (Conservation Biology, 2001)

An Assessment of the Focal‐Species Approach for Conserving Birds in Variegated Landscapes in Southeastern Australia - James Watson; David Freudenberger; David Paull (Conservation Biology, 2001)
The temperate woodlands of the northern Australian Capital Territory and bordering the New South Wales region of eastern Australia have been extensively disturbed by agriculture and urbanization. Small patches of woodland are now embedded in a pastoral or suburban matrix. Birds within landscapes of this region are threatened by a reduction in habitat area, increased isolation, and declining habitat condition. Within this setting, we assessed “focal species” approach for its ability to identify the minimum patch size, habitat structural complexity, and landscape connectivity required to accommodate existing woodland birds. Presence/absence data were gathered for 72 woodland remnants that varied in size, isolation, and habitat structural complexity. The Hooded Robin ( Melanodryas cucullata ) was identified as the focal species for the threats of area and resource limitation because it had the most demanding requirements for area (>100 ha) and habitat complexity. The eastern Yellow Robin ( Eopsaltria australis ) was the species most threatened by isolation of remnants. A landscape designed to meet the habitat requirements of these birds should encompass the requirements of all other woodland bird species that are sensitive to similar threats. A revegetation scenario based on the requirements of these two focal species is not feasible because the majority (>95%) of woodland remnants within the study area are too small, too lacking in habitat structural complexity, and too isolated to meet the requirements of the focal species. If woodland management guidelines concentrate on increasing small remnants to 10 ha in size and on ensuring that these remnants have complex shrub and ground‐layer vegetation and are not isolated by more than 1.5 km from neighboring remnants, the needs of at least 95% of the resident woodland bird species in the region should be accommodated. The focal‐species approach was effective for rapidly developing planning guidelines for the conservation of woodland birds in these variegated landscapes, and the approach is likely to be useful for guiding landscape reconstruction in other environments.

Pharmacokinetics of a Hematoregulatory Peptide (SK&F 107647) in Healthy Male Volunteers and in Patients with Colorectal or Pancreatic Adenocarcinoma Not Amenable to Standard Therapy - Parnian Zia-Amirhosseini; Robert Z. Harris; Hugh C. Cowley; Juan W. Valle; David R. Citerone; Venkata K. Boppana; Howard Scarffe; Philip Watson; Charles B. Davis (Pharmaceutical Research, 2000)

Studies on the dermal and systemic bioavailability of polycyclic aromatic compounds in high viscosity oil products - David Potter; Ewan D. Booth; Henk C. A. Brandt; Robert W. Loose; Robert A. J. Priston; Alan S. Wright; William P. Watson (Archives of Toxicology, 1999)

Cloning, Sequence, and Expression of the Phosphofructokinase Gene of Clostridium acetobutylicum ATCC 824 in Escherichia coli - Ed Belouski; David E. Watson; George N. Bennett (Current Microbiology, 1998)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

Purification and characterization of the recombinant CMP-sialic acid synthetase from Neisseria meningitidis - Michel Gilbert; David C. Watson; Warren W. Wakarchuk (Biotechnology Letters, 1997)

Biochemical responses to sediment-associated contaminants in brown bullhead (Ameriurus nebulosus) from the Niagara River ecosystem - NANCY A. Eufemia; TRACY K. Collier; JOHN E. Stein; DAVID E. Watson; RICHARD T. Di Giulio (Ecotoxicology, 1997)

Molecular dosimetry of DNA adducts in rainbow trout (Oncorhynchus mykiss) exposed to benzo(a)pyrene by different routes - David Potter; Thomas M. Clarius; Alan S. Wright; William P. Watson (Archives of Toxicology, 1994)

Book reviews - Jack M. Winters; Robert J. Morff; Charles S. Lessard; David E. Bergbreiter; Benjamin S. Kelley; Fertac Bilge; William A. Hyman; Brad D. Etter; Karan Watson; Timothy W. King; Carolyn A. Bradley; Yun S. Choi; et al. (Annals of Biomedical Engineering, 1990)